2002
DOI: 10.1046/j.1440-1746.17.s4.16.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of hepatitis B virus surface antigen mutants in Singapore patients with hepatocellular carcinoma and hepatitis B virus carriers negative for HBsAg but positive for anti‐HBs and anti‐HBc

Abstract: The existence of a more complex antigenic structure of HBsAg is indicated by the decreased reactivity to detection of mutations, some of which are outside the a-determinant, escape vaccination and may persist in seronegative patients. The high proportion of HBsAg mutants that are integrated in HCC genomes suggests a role of these mutants in hepatocarcinogenesis, possibly leading to mutant HBV-related HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…Only a few studies have addressed the questions of the rate of HBV mutations in tumor tissues (Pontisso et al, 1984;Raimondo et al, 1988;Clementi et al, 1993). However, our group and others have shown that mutations in basal core promoter, PreC/C, envelope and X sequences can be identified in HCC tissues (Minami et al, 1996;Fan et al, 2000Fan et al, , 2001Tu et al, 2001;Oon et al, 2002;Iavarone et al, 2003;Kao et al, 2003;Kuang et al, 2004). We have observed that in the Core gene, most of the non-synonymous mutations (i.e.…”
Section: The Role Of Hepatitis B Virus In Liver Cell Carcinogenesismentioning
confidence: 79%
“…Only a few studies have addressed the questions of the rate of HBV mutations in tumor tissues (Pontisso et al, 1984;Raimondo et al, 1988;Clementi et al, 1993). However, our group and others have shown that mutations in basal core promoter, PreC/C, envelope and X sequences can be identified in HCC tissues (Minami et al, 1996;Fan et al, 2000Fan et al, , 2001Tu et al, 2001;Oon et al, 2002;Iavarone et al, 2003;Kao et al, 2003;Kuang et al, 2004). We have observed that in the Core gene, most of the non-synonymous mutations (i.e.…”
Section: The Role Of Hepatitis B Virus In Liver Cell Carcinogenesismentioning
confidence: 79%
“…HBsAg escape mutations, such as G130D, T131N, M133T, and G145R, were found in patients who were positive for anti-HBs but negative for HBsAg (9,30). Oon et al (32) reported that HBV carriers, including HCC patients who were negative for HBsAg but positive for anti-HBc and anti-HBs, had the T126S, Q129D, M133L, T140I, and G145R mutations within the S region. Wu et al (31) reported that amino acid residues at positions 122 and 145 of HBsAg had a major effect on antigenicity and immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Such mutants have also been reported in association with escape from vaccineinduced immunity [Oon et al, 1995;Carman, 1997;Ho et al, 1998;Chong-Jin et al, 1999;He et al, 2001;Lee et al, 2001;Seddigh-Tonekaboni et al, 2001] and with failures of therapy with specific immunoglobulin in newborns from carrier women and in liver-transplant recipients [Harrison et al, 1994;Oon et al, 1996Oon et al, , 2002Brind et al, 1997;Carman, 1997;Ngui et al, 1997;Protzer-Knolle et al, 1998;Santantonio et al, 1999;Roznovsky et al, 2000;Liu et al, 2002]. The amino-acid substitution Gly145Arg has been reported most frequently [Francois et al, 2001], and is known to be stable [Zuckerman and Zuckerman, 1999].…”
Section: Introductionmentioning
confidence: 96%
“…Vaccine-induced immunity may also act as a selection factor that might lead to the emergence of particular mutants in the population. 'a' determinant mutants have been sought in selected patients Oon et al, 2002;Alhababi et al, 2003;Wagner et al, 2004], but few attempts have been made to estimate the prevalence of these mutants among unselected chronic carriers [Liu et al, 2002;Hsu et al, 2004;Song et al, 2005]. Such studies have been recommended recently [Gerlich, 2004].…”
Section: Introductionmentioning
confidence: 99%